PENGARUH MODAL INTELEKTUAL TERHADAP ECONOMIC VALUE ADDED PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009 – 2013 - MAYASANI, REYSITA (Jurnal Akuntansi AKUNESA, 2015)
The purpose of this study to analyze the influence of Intellectual Capital to Economic Value Added. This research was conducted on Pharmaceutical companies listed of Indonesian Stock Exchange in 2009-2013. The model that used to measure intellectual capital was using Modified Value Added Intellectual Coefficient (M-VAIC). M-VAIC component consist of Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), Relational Capital Efficiency (RCE), and Capital Employed Efficiency (CEE).This research is quantitative research and uses linear regression for data analysis. The results showed that Human Capital Efficiency (HCE) and Structural Capital Efficiency (SCE) has an impact to Economic Value Added (EVA) for a while Relational Capital Efficiency (RCE), and Capital Employed Efficiency (CEE)Keywords: Intellectual Capital, Modified Value Added Intellectual Coefficient (M-VAIC), Economic Value Added